‘Where do I begin the story?’: Collective memory, biographical authority and the rock biography - Strachan, Robert (Popular Music History, 2008)
This article is concerned with three main areas. Firstly it examines how the rock biography might be active in the creation of a collective memory of popular culture. Secondly, it examines how the stylistic conventions and institutional pressures of publishing have a major effect upon what type of narrative is constructed within the rock biography. Thirdly, the article is concerned with how audiences and fan cultures engage with those common narratives. Using Robert Shelton’s 1986 biography of Bob Dylan, No Direction Home as an example, the article argues that the biographer’s project necessitates the construction of a biographical authority which is achieved through the use of certain techniques and tropes. It will further suggest that this biographical authority is by no means stable and is affected by the biography’s reception in a wider critical landscape.